The impact of Composite Dietary Antioxidant Index on the relationship between eczema and depression symptoms in US adults - Zhang, Tian; Zhang, Ruohua; Song, Ting; Chen, Fang; Wei, Yuegang (Frontiers in Nutrition, 2024)
The study aims to explore the associations of eczema, Composite Dietary Antioxidant Index (CDAI), with depression symptoms in adults based on the National Health and Nutrition Examination Surveys (NHANES) database.In total, 3402 participant data were extracted from the NHANES 2005-2006. The relationship between eczema, CDAI, and depression symptoms was explored by utilizing weighted univariate and multivariate logistic regression models, presenting as odds ratios (ORs) and 95% confidence intervals (CIs). The additive interaction between eczema, CDAI, and depression symptoms was measured by relative excess risk due to interaction (RERI) and the attributable proportion of interaction (AP). Subsequently, the associations of eczema, CDAI, with depression were also explored in different gender, body mass index (BMI), and smoking subgroups.Results: Of the 3402 participants included, the mean age was 46.76 (0.83) years old, and 174 (5.11%) participants had depression symptoms. In the adjusted model, both eczema (OR=3.60, 95%CI: 2.39-5.40) and CDAI (OR=1.97, 95%CI: 1.19-3.27) were associated with a higher prevalence of depression symptoms. Compared to the participants with high CDAI and no eczema, those participants with low CDAI (eczema: OR=7.30, 95%CI: 4.73-11.26; non-eczema: OR=1.84, 95%CI: 1.06-3.19) have higher odds of depression symptoms, no matter have eczema or not. When under low CDAI levels, eczema was associated with increased odds of depression symptoms (OR=3.76, 95%CI: 2.34-6.03). When under low CDAI level, eczema was also related to elevated odds of depression symptoms in those males, females, BMI <25, BMI ≥25, non-CDAI in the association of eczema with depression symptoms 4 smoking, and smoking.CDAI could modulate the association of eczema with depression symptoms in adults.